2017
DOI: 10.1098/rstb.2016.0044
|View full text |Cite
|
Sign up to set email alerts
|

Resistance in persisting bat populations after white-nose syndrome invasion

Abstract: Increases in anthropogenic movement have led to a rise in pathogen introductions and the emergence of infectious diseases in naive host communities worldwide. We combined empirical data and mathematical models to examine changes in disease dynamics in little brown bat ( Myotis lucifugus ) populations following the introduction of the emerging fungal pathogen Pseudogymnoascus destructans , which causes the disease white-nose syndrome. We found that infection inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 61 publications
(121 reference statements)
2
125
0
Order By: Relevance
“…; Langwig et al . ). In fact, a recent study showed that many populations of R. sierrae that experienced Bd‐induced population declines over the last four decades are recovering in the presence of Bd, but with reduced Bd loads relative to naive populations (Knapp et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Langwig et al . ). In fact, a recent study showed that many populations of R. sierrae that experienced Bd‐induced population declines over the last four decades are recovering in the presence of Bd, but with reduced Bd loads relative to naive populations (Knapp et al .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, when managing disease‐induced declines and extinctions, it may be important to manage not only for the transmission dynamics, but also the level of host tolerance and resistance in a population (Kilpatrick ; Langwig et al . , ; Epstein et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, this suggests that some colonies of M. lucifugus and P. subflavus may have become tolerant to the fungus, whereas others may have become resistant (Langwig et al. ). Another species, M. sodalis , had high prevalence but loads consistent with less‐impacted species (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we instead expect the strongest and most consistent directional selection to arise when humans instigate or intensify escalating arms races, such as when we kill or control our enemies (weeds, pests, pathogens), which then evolve resistance, which thus necessitates newer or stronger control measures-and so on [30,36,38]. Even here, directional selection might stop-or at least weaken-if, for example, enemies evolve tolerance instead of resistance [39,54,61], if they evolve to become friends or neighbours (e.g. domestication of wild animals or plants [62,63]), or if we wipe them out.…”
Section: Human Influences On Evolution (Figure 3)mentioning
confidence: 99%